Protocols for Mechanical Cleaning of the Post Space on the Bond Strength Between Root Dentin and Cementation System - Alencar, C. M. [UNESP]; Verbicario dos Santos, J. R. E. [UNESP]; Jasse, F. F. A.; Dos Santos, G. O.; Escalante-Otarola, W. G.; Castro-Nunez, G. M.; Campos, E. A. de [UNESP]; Kuga, M. C. [UNESP] (Operative Dentistry Inc, 2021)
Objective: To evaluate the effects of mechanical versus chemical cleaning protocols for cleaning the root dentin surface before cementation of fiberglass posts for their effect on the bond strength, failure mode, and dentinal penetration of the cementing agent using an etch-and-rinse adhesive system on dentin prepared to receive a fiberglass post. Methods: Forty roots of bovine teeth were endodontically treated and prepared for fiber post cementation. The specimens were randomized into 4 groups of 10: Control group (CO) - irrigation with 2.5% NaOCl; DW group- irrigation with distilled water; RB group - rotating brush for cleaning root canals, and CUI group - continuous ultrasonic irrigation. The fiberglass posts were cemented, and the specimens were immersed in distilled water for 6 months. A push-out test was performed on the cervical, middle, and apical thirds of the samples. Dentinal penetration of the cementing agent and the fracture pattern were evaluated by laser confocal microscopy. Statistical analysis was performed using analysis of variance (ANOVA) and post hoc Tukey tests (alpha=0.05). Results: The RB and CUI groups showed significantly higher bond strength values when compared to the Control and DW groups (p<0.05). In addition, in the control and DW groups, the apical third presented lower bond strength values when compared to middle and cervical thirds. Conclusion: While DW showed the highest incidence of adhesive type failure, CUI resulted in the highest dentinal penetration of the cementing agent (p<0.05). RB and CUI resulted in the highest bond strength between cementation system and root dentin. In addition, CUI favored greater dentinal penetration of fiberglass post cementing agent.